Sacra et profana: permanências e transformações no pátio de São Pedro em Recife-PE - Nascimento Neto, Josebias Costa do (2023)
The present research fits into the field of work of the cultural heritage of Pernambuco with the expectation of providing contributions regarding the São Pedro courtyard in Recife, PE. Designated as the empirical object of this study, the aim is to insert this research into the debate on the continuities and transformations that at times alter and devalue a heritage site, but at other times redefine its meaning and respective values. This contributes to ensuring that the site remains meaningful to society. Based on these observations and reflections, the overarching goal of the investigation was formulated: starting from and referencing the values listed by IPHAN in the listing processes that declared the Concatedral of São Pedro dos Clérigos and its respective courtyard as a national heritage, to examine what still ensures, today, its status as a culturally significant heritage for the city of Recife. Therefore, the attempt is to understand how the São Pedro courtyard, amid changes and continuities, has survived and transformed over the period of its listing without losing its character as a cultural heritage. Through a historical, descriptive, and analytical-interpretative approach, the research revisited the values attributed to the mentioned courtyard in its listing, in addition to observing its patterns of use, morphology, and image. This investigation methodologically unfolds across three inseparable dimensions: historical, spatial, and symbolic, with the aim of understanding how and why the courtyard remains a hub for cultural manifestations in Recife, which, though evolving over time, have provided support for the preservation of this emblematic urban space.